Effect of Chitosan Edible Coating on the Microbial Quality of Ribbonfish, Lepturacanthus savala (Cuvier, 1929) Steaks - Renuka, V.; Mohan, C. O.; Kriplani, Y.; Sivaraman, G. K.; Ravishankar, C. N. (Fishery Technology, 2016)
The demand for healthy food products without anyadded chemical preservative is increasing globally.Chitosan can find application in food products due toits bio-preservation effects. The present study wasaimed to assess the effectiveness of chitosan ediblecoating on the microbial quality of ribbon fish,Lepturacanthus savala. Ribbonfish steaks treated with(1%) and without chitosan were packed in multilayeredfilms and stored under refrigerated conditions(3Â±1oC). The fish used in the study is mediumfatty fish with good quantity of crude protein. Theinitial total plate count of 4.5 log cfu g-1 indicates thegood quality of fish used in the study which exceededlimit of 7 log cfu g-1 on 10th days in control samplesindicating the shelf life of ~8-9 days. In chitosantreated samples, total plate counts were observed tobe 6.81 log cfu g-1on 15th day and the limit of 7 log cfug-1was exceeded only on 20th day indicating a shelflife of ~16-17 days. This clearly indicates the antimicrobialeffect of chitosan. Further, significantly (p